An Ethnographic Study of Papadjab, an Afro-Caribbean Devil Dancer The Christmas Street Festival in St. Lucia. - Wintersteen, Benjamin (Lewiston : Edwin Mellen Press, 2010)
This book examines the religious, mythological and performance elements of the traditional Afro-Caribbean street festival. Using the theories of performance, political economy and symbolic analysis, this work elucidates how elements of African, European and South American cultures interact to produce a unique understanding of the colonial and post-colonial experience.
Description based upon print version of record.
Keywords: Christmas -- Saint Lucia; Devil -- Folklore; Devil -- Social aspects -- Saint Lucia; Festivals -- Saint Lucia; Saint Lucia -- Social life and customs; Christmas -- Saint Lucia; Festivals -- Saint Lucia; Devil -- Social aspects -- Saint Lucia; Folklore -- Saint Lucia; Saint Lucia -- Social life and customs; RELIGION / Holidays / Christmas & Advent; Electronic books